AKTIFITAS ANTIOKSIDAN DAN ANTIKOAGULASI RESIN JERNANG - Totok K. Waluyo; Gunawan Pasaribu (Jurnal Penelitian Hasil Hutan, 2013)
Dragon's blood is essentially a red-colored resin secreted by the fruits of rattan species. The dragon's blood originated from Indonesia which becomes widespread in international market is indigenous from Daemonorops spp. The dragon's blood has been popularly used as traditional medicines. To confirm such dragon's blood efficacy, an assesment was already conducted regarding the phytochemical screening, antioxidant activity, and anticoagulant activity indicatively afforded by the dragon's blood resin produced by three rattan species, ie. Daemonorops longipes Mart, Daemonorops draco BL, and Daemonorops melanochaetes BL. Phytochemical screening aimed to identify the kinds of chemical compounds inside the dragon's blood resin; antiæcidant tests used DPPH (2,2-diphenyl-1-picrylhydrazyl); and anticoagulation tests proceed in-vitro using rabbit blood. Results revealed that the dragon's blood from those three species, exctracted using polar (methanol) and semi-polar (ethyl acetate) solvents, contained chemical compounds which are already renowed for medicinal efficacy and potent antinccidant, e.g. flavonoids, triterpenoids, and tannin. The greatest antioccidant potency was imparted by dragon's blood from Daemonorops longipes Mart, as indicated by its lowest IC value (71.89U+3,89 mgl.). The ethyl acetate dragon's blood extract, rather than promoting anticoagulat action on the rabbit-blood, in fact induced the blood coagulation, whereby the extract from Daemonorops longipes Mart performed the most effectively (shortest in coagulation time).